Determinants of outsourcing domestic labour in conservative welfare states: Resources and market dynamics in Germany - Karen A. Shire; Rainer Schnell; Marcel Noack (Universität Duisburg-Essen, Institut für Soziologie, 2017)
Women in conservative welfare states continue to do more unpaid domestic labour than their partners. Many European countries subsidize the outsourcing of routine housework and care labor to market services through tax credits and other measures, with the aim of reducing women's unpaid work. Most research on the determinants of outsourcing replicate gendered exchange-bargaining models, and neglect market factors relevant to explaining the substitution of unpaid labour. The neglect of market factors however, is mainly due to data limitations. Drawing on a new data set in the German Socio-Economic Panel Innovation Study (SOEP-IS) develop models, which include market as well as resource factors in examining the determinants of outsourcing domestic labour. The analyses confirm previous research findings, that households with more resources are more likely to outsource. Thus, the availability of tax credits for household purchases does not seem to encourage households with lower incomes to shift unpaid domestic labour to the market. In contrast to previous research findings based on exchange-bargaining theory, relative resources of women are neither predictors of more or of less outsourcing. Models explaining the gendered division of labour are not necessarily transferable to the study of outsourcing unpaid labour to the market. Previous research in Germany finds that partners revert to traditional gendered divisions of labour when they become parents. We find that the presence of young children increases the probability of outsourcing, suggesting that buying-in services may be a way in which re-traditionalization is averted. Overall, market factors have a strong impact on whether households outsource or not, especially demand for eldercare and the availability of services. Yet most labour available to German households is not supplied by the service sector, but from the black market. The article concludes that future research needs to address the interaction of demand and supply side factors, ideally in cross-national household-level analyses.
Keywords: 300; domestic labour; gender; eldercare; informal employment; migrant domestic labour